Improving Antibiotic Prescribing in Bangladesh Comparing with the United Kingdom: A Systematic Review (Medicine Today, 2025)
Antimicrobial resistance (AMR) has emerged as a significant global public health threat, jeopardizing the effectiveness of antibiotics and complicating the treatment of infectious diseases. The World Health Organization (WHO) has identified AMR as a critical issue, attributing its rise to factors such as overprescribing, self-medication, and inadequate antimicrobial stewardship (AMS) practices. In low- and middle-income countries (LMICs) like Bangladesh, the challenge is exacerbated by limited healthcare infrastructure, a high prevalence of informal healthcare providers, and a lack of awareness regarding the responsible use of antibiotics.In contrast, high-income countries such as the United Kingdom have implemented structured AMS frameworks aimed at promoting rational antibiotic prescribing and reducing unnecessary use. Initiatives like the TARGET Antibiotic Checklist have been effective in improving physician practices and enhancing patient education, leading to better health outcomes and a reduction in AMR. This systematic review seeks to compare AMS practices and antibiotic prescribing patterns in Bangladesh and the UK, highlighting the disparities in awareness, knowledge, and implementation of AMS strategies. By examining the current state of antibiotic use in both countries, the review aims to identify key challenges and propose actionable recommendations to improve AMS efforts, particularly in LMICs where the burden of AMR is most acute.Medicine Today 2025, Vol.37 (1): 133-143